2007
DOI: 10.1111/j.1600-0765.2007.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compression force on fibroblast growth factor‐2 and receptor activator of nuclear factor kappa B ligand production by periodontal ligament cells in vitro

Abstract: Fibroblast growth factor-2 may be partly involved in osteoclastogenesis during orthodontic tooth movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 54 publications
2
39
0
1
Order By: Relevance
“…The results of the current study indicate that various fibroblastic cells naturally produce OPG, thereby supporting the inhibitory roles of fibroblasts on osteoclastogenesis. There are also significant findings showing that mechanical force induces the production of both OPG and RANKL by PLF, while OPG is predominant over RANKL [Yamamoto et al, 2006;Nakajima et al, 2008;Kook et al, 2009]. Importantly, however, the results from GCF analysis showed that the levels of RANKL are naturally higher than those of OPG in this cell type.…”
Section: Discussionmentioning
confidence: 68%
“…The results of the current study indicate that various fibroblastic cells naturally produce OPG, thereby supporting the inhibitory roles of fibroblasts on osteoclastogenesis. There are also significant findings showing that mechanical force induces the production of both OPG and RANKL by PLF, while OPG is predominant over RANKL [Yamamoto et al, 2006;Nakajima et al, 2008;Kook et al, 2009]. Importantly, however, the results from GCF analysis showed that the levels of RANKL are naturally higher than those of OPG in this cell type.…”
Section: Discussionmentioning
confidence: 68%
“…They also performed an in vitro study and reported that compression stressed PDL cells increased the secretion of RANKL in a time-dependent manner but decreased the secretion of OPG in a time-dependent manner. Nakajima et al 33 carried out a similar compressive stimulation study on PDL cells. They also reported that RANKL production was elevated in a time and force-dependent manner up to 4 g/cm 2 , the maximal force that they used.…”
Section: Discussionmentioning
confidence: 99%
“…The compressive force is adjusted by adding lead granules to the bottle to allow PDLCs to be subjected to 2.0 g/cm 2 of compressive force, and the force is maintained for 0.5, 3, 6, or 12 hours, respectively. 3,18 These time points were selected according to the method described in our previously published article. 19 Two and a half microliters of GsMTx4 (Abcam, San Francisco, CA, USA), a specific inhibitor of cationic mechanosensitive ion channels, was added, and 0.8 ng/mL of TNF-a (R&D, Shanghai, China) was added to the indicated groups.…”
Section: Mechanical Stimulation: Application Of Static Compressive Forcementioning
confidence: 99%
“…This method comprises a modification of the method described by Hiroyuki and Li. 3,5,18 Briefly, a cover glass and a glass bottle are placed on the monolayer hPDLCs. The compressive force is adjusted by adding lead granules to the bottle to allow PDLCs to be subjected to 2.0 g/cm 2 of compressive force, and the force is maintained for 0.5, 3, 6, or 12 hours, respectively.…”
Section: Mechanical Stimulation: Application Of Static Compressive Forcementioning
confidence: 99%